أنماط التعلق و علاقتها بالادمان على الانترنت لدى عينة من طلبة كلية العلوم الاجتماعية بالأغواط - بلخضر شيماء; سحيري زينب (My University, 2019)
The present study aimed to identify the relationship between attachment patterns (safe, avoidance, anxiety) and online addiction among students of the Faculty of Social Sciences at Laghouat University, in addition to the differences detection of the Internet according to gender variables and specialization. The sample consisted of 98 male and female students at the Faculty of Social Sciences at laghouat. The Yarmouk attachment scale was used for Abogazal and Djradat the module of online addiction scale, which was prepared by researcher Bellkhadar chaima. In this study, the descriptive approach was adopted as the most suitable for this study. It allows for a precise description of attachment and addiction patterns on the Internet, and expresses these variables in quantity and quality, and thus results are extracted, evaluated and tested. The results of the study after using the statistical method Pearson correlation coefficient indicated that there was a correlation between the attachment and online addiction patterns of the sample. After analyzing the data and using it in a statistical way using the T test (for two different tests), we obtained the following results: There is an inverse correlation between attachment style anxiety and online addiction. There is no correlation between the style of safe attachment and online addiction There is no correlation between the pattern of avoidance attachment and online addiction.There were no statistically significant differences between males and females in online addiction. There are no statistically significant differences in online addiction depending on the specialization variable